Problematika Pembiayaan Mudharabah di Perbankan Syariah Indonesia - Gugun Sodik; Ahmad Hasan Ridwan (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The application of Islamic economic principles in Islamic banking, with Mudarabah financing as a key instrument, presents a financial model based on justice and sustainability. Nevertheless, Mudarabah financing faces a series of challenges that may hinder its potential. This paper investigates several issues, including the lack of understanding among the public and entrepreneurs, difficulties in determining profit-sharing ratios, business risks, unclear regulations, as well as ethical and social responsibility issues. Various solutions are proposed, such as enhancing understanding through education, drafting clear agreements, developing comprehensive regulations, involving the community in oversight, and emphasizing business ethics and social responsibility. By addressing these challenges, it is anticipated that Mudarabah financing can be optimized to support an inclusive and sustainable economy within the framework of Islamic banking.